Ideal strength of nanoscale materials induced by elastic instability. (January 2020) - Ho, Duc Tam; Kim, Soon; Kwon, Soon-Yong; Kim, Sung Youb
Abstract: The ideal strength of a defect-free material, which is the stress causing a material failure, is one of the fundamental mechanical properties. In this study, we investigate ideal strengths of some face-center cubic nanostructures using molecular statics simulations and an elastic stability criterion. The simulation results show that ideal strength depends strongly on loading direction, loading mode (tension or compression), side surface orientation, shape of cross-section, and size. Consequently, nanostructures can exhibit the "smaller is stronger" trend, the "smaller is weaker" trend, and the "size-independent strength plateau" trend. Our semi-analytic model for prediction of ideal strengths of nanostructures is in good agreement with molecular statics simulation results.